Conceptual Understanding in Static Fluid through the Recitation Program for Students at SMA Ar-Rohmah International Islamic Boarding School - Maghfiroh, Alifiyah Nindi; Putri, Febi Dwi; Purwaningsih, Endang; Taqwa, Muhammad Reyza Arief (Program Studi Pendidikan IPA, Universitas Islam Lamongan, 2023)
Conceptual understanding of physics is one of the important factors to improve the quality of learning physics. However, several studies have shown that studentâ€™sÂ conceptual understanding is low, especially in static fluid material. Several studies have attempted to use recitation programs and have succeeded in increasing understanding of the concept. Student's conceptual understanding can be improved through independent learning. Independent learning can use recitation programs, but not many available static fluid recitation programs are equipped with concept explanations and do not yet cover students who study in a formal and boarding school system, such as boarding school students. Existing recitation programs are widely used by students to support independent learning. Recitation of students is still rare because of the lack of independent learning. Therefore, this study aims to improve boarding school studentâ€™s conceptual understanding in static fluid material through recitation program. This research is quantitative research with a quasi-experimental and one group pretest-posttest design. The recitation program is given in the form of an interesting computer-assisted animation outside of learning. The subjects of this study were 40 students of class XI Natural Science 1 at the SMA International Islamic Boarding School Ar-Rohmah Dau, Malang. The research instruments included valid recitation programs and pretest-posttest questions. Data obtained from the results of the conceptual understanding test supported by interviews. The results showed that there was an increase in students' understanding of the concept which was calculated through an N-gain of 0.45 in the medium category and an effect-size of 1.68 in the strong category. The findings of this study imply that the recitation program can improve student's understanding of concepts like previous research, and practically that teachers can utilize the recitation program as student learning material.